Transcriptome and Metabolome Analyses Reveal Complex Molecular Mechanisms Involved in the Salt Tolerance of Rice Induced by Exogenous Allantoin - Juan Wang; Yingbo Li; Yinxiao Wang; Fengping Du; Yue Zhang; Ming Yin; Xiuqin Zhao; Jianlong Xu; Yongqing Yang; Wensheng Wang; Binying Fu (MDPI AG, 2022)
Allantoin is crucial for plant growth and development as well as adaptations to abiotic stresses, but the underlying molecular mechanisms remain unclear. In this study, we comprehensively analyzed the physiological indices, transcriptomes, and metabolomes of rice seedlings following salt, allantoin, and salt + allantoin treatments. The results revealed that exogenous allantoin positively affects the salt tolerance by increasing the contents of endogenous allantoin with antioxidant activities, increasing the reactive oxygen species (ROS)-scavenging capacity, and maintaining sodium and potassium homeostasis. The transcriptome analysis detected the upregulated expression genes involved in ion transport and redox regulation as well as the downregulated expression of many salt-induced genes related to transcription and post-transcriptional regulation, carbohydrate metabolism, chromosome remodeling, and cell wall organization after the exogenous allantoin treatment of salt-stressed rice seedlings. Thus, allantoin may mitigate the adverse effects of salt stress on plant growth and development. Furthermore, a global metabolite analysis detected the accumulation of metabolites with antioxidant activities and intermediate products of the allantoin biosynthetic pathway in response to exogenous allantoin, implying allantoin enhances rice salt tolerance by inducing ROS scavenging cascades. These results have clarified the transcript-level and metabolic processes underlying the allantoin-mediated salt tolerance of rice.